The Implementation of Doctor-Patient Role-Playing to Enhance the Socio-Emotional Development of Children Aged 5–6 Years - Henti Susanti Dewi; Syahrul Ismet; Yaswinda; Vivi Anggraini (Jurnal CARE (Children Advisory Research and Education), 2026)
Social-emotional development is a crucial aspect of early childhood education, playing a vital role in shaping the ability to cooperate, empathize, and interact positively with the social environment. Preliminary observations in Group B at Mawar Sari Kindergarten, North Bengkulu, revealed that most children exhibited egocentric behavior, a reluctance to share, an inability to cooperate, and difficulty waiting for their turn. This study aimed to analyze improvements in the social-emotional development of young children—specifically regarding cooperation and empathy—through the implementation of a doctor-patient role-play method. The study employed the Kemmis and McTaggart Classroom Action Research (CAR) model, conducted over two cycles comprising planning, action implementation, observation, and reflection. The subjects consisted of 10 children purposively selected from a group of 33 based on their low social interaction skills. Data were collected through observation, interviews, and documentation, then analyzed using both qualitative and quantitative descriptive methods, including mastery percentage calculations. The results showed an improvement in cooperation and empathy skills from 20% in the pre-cycle stage to 50% in Cycle I, rising further to 80% in Cycle II. These findings indicate that the doctor-patient role-play method is effective not only in enhancing cooperation and empathy but also in providing a learning experience that encourages children to communicate, collaborate, understand others' perspectives, and develop prosocial behaviors in their daily lives; furthermore, this method serves as a contextual and enjoyable alternative teaching strategy for early childhood education institutions.